The Ghost Of Black Wood Hall - Keene Carolyn; Carolyn Keene (New York Carolyn Keene, 1948)
Nancy Drew investigates a series of, apparently, supernatural hauntings and jewelry thefts targeting vulnerable women, including Mrs. Putney.
Keywords: The Ghost of Blackwood Hall by Carolyn Keene, the "ghost" is actually a fraudulent, cruel hoax designed to swindle gullible people; the danger of gullibility and the importance of skepticism when faced with seemingly supernatural events or charismatic manipulation